Multifaceted Social and Environmental Disruptions Impact on Smallholder Plantations’ Resilience in Indonesia - Apri Andani; Irham Irham; Jamhari Jamhari; Any Suryantini (The Scientific World Journal)
As one of the most productive plantation producers in the world, Indonesia also faces rapid change in both social and environmental systems. These conditions are predicted to become more disruptive to the agricultural sector in the future. Therefore, understanding the impact of social and environmental disruption on smallholder plantations’ resilience is vital to formulate a strategy for the sustainability of farmers’ livelihoods in this country. Using survey data from 360 smallholding farmers in six villages from three districts in Bengkulu Province, Indonesia, the study deployed a multidimensional approach to assess smallholders’ resilience to social and environmental disruption as well as towards economic dynamics. There are four dimensions of smallholder resilience, namely, the ability of adaptation, recoverability, anticipation, and farmers’ innovation level. Social disruption was indicated by farmers’ demography, epidemic/family health, social conflict, culture clash, and intention on land conversion. Meanwhile, environmental disruption was shown by natural catastrophe incidents, climate variations, environmentally unfriendly cultivation activities, and land fires. Since the resilience level was classified as binary, bivariate probit model was used in the analysis. The result shows that smallholder plantations in Bengkulu Indonesia are categorized as innovative, and recoverable, but less adaptive, and less anticipatory farmers. Overall, more than 50% of smallholder plantations are classified as less resilient smallholders. The statistical result empirically uncovers that the intentions of land conversion, climate change, and environmentally unfriendly farming activities statistically have a significant contribution to the reduction of smallholder plantations’ resilience. Furthermore, the economic dynamisms such as lack of input availability, price volatility, demand uncertainty, and capital limitation have a significant negative impact on smallholder plantation resilience.